ANALISIS EFEKTIVITAS PELAYANAN KESEHATAN PROGRAM BPJS DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKATDI INDONESIA - Futri Ritonga; Widya Kinanti, Supriati Munthe, Fitriani Pramita Gurning (CV. Adiba Aisha Amira, 2024)
A person's health is very important in life. In addition, good health is supported by adequate and superior facilities. In addition, the insurance industry needs to provide services that provide protection for humans, especially those related to activities that are beneficial to public health. The aim of this research is to determine the benefits that the community obtains from the program, whether the program provides adequate health protection, and whether this program really causes an increase in welfare for the community as a whole. The method used is to analyze articles published in the last 5 years through Google Scholar, Sinta, and Garuda searches. The results of this research are that there are still many people who do not fully use BPJS. According to the journals collected, more than 50% of the services and facilities provided by hospitals and health centers are not fully complete and there are still many deficiencies. The public has the right to use health service data sources that are safe, high quality and affordable. Whether in health or illness, the quality of human growth and development is improved through access to quality health services.